2018
DOI: 10.3389/fnins.2018.00357
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A7 Levels Increase in Rats With Traumatic Brain Injury and Promote Secondary Brain Injury

Abstract: The incidence of traumatic brain injury (TBI) has been increasing annually. Annexin A7 is a calcium-dependent phospholipid binding protein. It can promote melting of the cell membrane. Recent studies have shown that it plays an important role in atherosclerosis, other cardiovascular diseases, and a variety of tumors. However, few studies of ANXA7 in TBI have been performed. We here observed how ANXA7 changes after TBI and discuss whether brain injury is associated with the use of ANXA7 antagonist intervention.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 22 publications
(23 reference statements)
1
12
0
Order By: Relevance
“…In this model, ANXA7 knockdown in vivo showed rescue effects on neuronal death, blood–brain barrier damage, brain edema, neurobehavioral deficient, and inflammatory response. Similar results were also obtained after subarachnoid hemorrhage-induced brain injury [ 383 ] and correlate with elevated AnxA7 levels in traumatic brain injury [ 384 ], making AnxA7-based therapies a potentially novel and alternative approach in the treatment of cerebrovascular disease ( Table 7 a).…”
Section: Anxa7supporting
confidence: 73%
“…In this model, ANXA7 knockdown in vivo showed rescue effects on neuronal death, blood–brain barrier damage, brain edema, neurobehavioral deficient, and inflammatory response. Similar results were also obtained after subarachnoid hemorrhage-induced brain injury [ 383 ] and correlate with elevated AnxA7 levels in traumatic brain injury [ 384 ], making AnxA7-based therapies a potentially novel and alternative approach in the treatment of cerebrovascular disease ( Table 7 a).…”
Section: Anxa7supporting
confidence: 73%
“…Many investigations indicated that secondary damage result in neuronal apoptosis is the main reason of poor outcome after TBI which is progressive from hours to days . Many pathological process were reported to be related to the neuronal apoptosis in the secondary damage . So, relieve of neuronal apoptosis was the fundamental therapy purpose of TBI.…”
Section: Introductionmentioning
confidence: 99%
“…Many investigators have indicated that secondary damage, which is progressive from hours to days, results in neuronal apoptosis and is the primary reason for poor TBI outcomes . Many pathologic processes were reported to be related to neuronal apoptosis during the secondary damage . So, relieving neuronal apoptosis has been instituted as a fundamental therapy for TBI.…”
Section: Introductionmentioning
confidence: 99%
“…2 Many pathologic processes were reported to be related to neuronal apoptosis during the secondary damage. 3,4 So, relieving neuronal apoptosis has been instituted as a fundamental therapy for TBI. However, despite much research on possible mechanisms, an effective treatment has not been found.…”
Section: Introductionmentioning
confidence: 99%